Improving written linguistic competence in EFL classrooms through self regulated error correction activities for young upper beginner ecuadorean learners from the teens programme at the english learning Institute COPEI. - Rivera Villa, Dennis Alessandro (2014)
To assess the academic and emotional effects grammar error correction techniques were having in the writing skills of students from the English Language Institute COPEI in the city of Guayaquil, in Ecuador, the objective of this thesis work was to analyse the direct error correction approach used therein with three groups of upper intermediate EFL teenage students. After having collected information from teachers and students using different instruments such as surveys and interviews, a worksheet that combined self regulated learning (SRL) and metalinguistic comments based on recent research was developed and applied to a fourth group. From the assessments to these four groups under study it was discovered that direct feedback helped the learners improve their grammatical knowledge but had no effect in long term learning. On the other hand; the application of the proposed research-based error correction activity helped the learners improve their grammar in writing on both short and long term. The findings of this work are relevant to EFL teacher and educational researchers who could use the proposed activity to deepen improved corrective feedback and foster learning.